2022
DOI: 10.1101/2022.07.22.501141
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 omicron variants succumbin vitrotoArtemisia annuahot water extracts

Abstract: The SARS-CoV-2 (COVID-19) global pandemic continuous to infect and kill millions while rapidly evolving new variants that are more transmissible and evading vaccine-elicited antibodies. Artemisia annua L. extracts have shown potency against all previously tested variants. Here we further queried extract efficacy against omicron and its recent subvariants. Using Vero E6 cells, we measured the in vitro efficacy (IC50) of stored (frozen) dried-leaf hot-water A. annua L. extracts of four cultivars (A3, BUR, MED, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Several groups have reported that extracts of A. annua and A. afra have potent anti-SARS-CoV-2 activity. 25,26,28–30 All testing thus far has been in vitro using hot water and/or solvent extracts of A. annua .…”
Section: Therapeutic Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have reported that extracts of A. annua and A. afra have potent anti-SARS-CoV-2 activity. 25,26,28–30 All testing thus far has been in vitro using hot water and/or solvent extracts of A. annua .…”
Section: Therapeutic Examplesmentioning
confidence: 99%
“…Nair et al has continued to test the original (frozen) DLAe samples for efficacy against emerging SARS-CoV-2 variants including delta, 26 omicron, and BA.4 30 and to date the A. annua hot water extracts have remained potent. Although thus far there is no identification of the non-artemisinin active phytochemicals, there are several likely candidates including isorhamnetin, luteolin, and rosmarinic acid, which are present in A. annua with IC 50 values of 8.42, 11.81, and 9.43 μM, respectively, against 3CLpro, the main chymotrypsin-like protease involved in SARS-CoV-2 viral replication.…”
Section: Therapeutic Examplesmentioning
confidence: 99%
“…If caffeic acid is a principal antiviral agent (or an effective proxy for antiviral activity) then Gecofure should have greater antiviral potency than Spice. This would be reminiscent of the situation for sweet wormwood (Artemisia annua) and African wormwood (Artemisia afra), which contain high or low amounts of artemisinin, respectively [44][45][46].…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%
“…It has also been shown that the use of whole plant preparations could help combat the emergence of artemisinin-resistant parasites because the crude mixture contains a range of additional antimalarial compounds that complement or synergize with artemisinin [41][42][43]. Wormwood leaf preparations, including preparations of Artemisia species that don't contain artemisinin, have also been shown to block SARS-CoV-2 infection at a step downstream of infectious entry in cell culture systems [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%